The Correlation Between Problem Focused Strategies Coping With Children’s Parent Resilience Cancer Patients Adam Malik Hopital - Suci Cahyani; Merri Hafni (JITSS (Journal of Innovation and Trend in Social Sciences), 2024)
Parents who care for children with cancer need the ability to rise from unexpected situations, namely resilience. Being a resilient individual involves effective coping strategies in dealing with stressful conditions. This research aims to determine the correlation between coping strategies and resilience in parents of children with cancer at Adam Malik Hospital. This research uses quantitative methods. The sample in this study were 70 parents of children with cancer at Adam Malik Hospital. Data collection in this study used two scales, namely the Connor-Davidson Resilience Scale (CD-RISC) and the problem focused coping strategy scale. The data analysis method used in this study is Product Moment Correlation. Based on the results of the product moment test, the correlation coefficient = 0.690 and the coefficient of determination = 0.476. These results indicate that there is a positive correlation between problem focused coping strategies and resilience with an effective contribution of 47.6%. This means that the resilience of parents of children with cancer in Adam Malik Hospital is 47.6% determined by the problem focused coping strategy factor.